1965
DOI: 10.1002/pssb.19650110122
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional and X‐Ray Diffraction Changes in Irradiated Single Crystal BeO

Abstract: Single crystals of B e 0 were irradiated by high energy (2 1 MeV) neutrons to doses of 102" t o 6:. 102O nvt a t low temperature (< 100 "C). The crystal structure effects of irradiation were examined by X-ray diffraction and measurement of interfacial angles between crystallographic faces. The diffraction patterns are characterized by duplex reflect,ions each composed of a sharp and a broad component. The sharp component is attributed to t,he matrix crystal volume, which is expanded by a random distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…4,26,40,41After irradiation, brighter intragranular regions in Ti 3 SiC 2 were observed in orientations parallel and normal to the a-axis.Figures 5(e) and (f) show higher magnification images of the "intragranular regions" that have the same contrast as TiC(1-x) in the as-received material. Tallman et al observed basal plane ½<0001> strain-field nanometric dislocation or antisite loops at 0.1 and 0.4 dpa 17,35,36. This is consistent with the planar component to defects in hcp ceramics.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…4,26,40,41After irradiation, brighter intragranular regions in Ti 3 SiC 2 were observed in orientations parallel and normal to the a-axis.Figures 5(e) and (f) show higher magnification images of the "intragranular regions" that have the same contrast as TiC(1-x) in the as-received material. Tallman et al observed basal plane ½<0001> strain-field nanometric dislocation or antisite loops at 0.1 and 0.4 dpa 17,35,36. This is consistent with the planar component to defects in hcp ceramics.…”
mentioning
confidence: 65%
“…33,34 In BeO, data extrapolated to T irr ~400°C revealed Δc/c values that saturated at ~2.5%, while Δa/a was in the order of -0.1%. 33,34 The theories to explain the c-axis increase in BeO show similarities to Ti 3 SiC 2 ; Sabine, Austerman and Miller et al all proposed planar defect clusters but were unable to agree on configuration, but the reported size (7.5 nm) was consistent with low dose microstructures seen by Tallman et al 17,35,36 As T irr increases, volumetric swelling (ΔV/V) due to LP changes in BeO were reduced due to increased defect mobility (which promoted point defect recombination), and lattice swelling saturated to values that were dependent on temperature, because defects were thermally dissipated as they were produced. 33,34 LP values in Figure 4 suggests that in Ti 3 SiC 2 , this begins from T irr ~ 550-700°C, which was unfortunately below the radiation temperature in this study, and is the subject of future isochronal annealing.…”
mentioning
confidence: 96%
“…For more details about diffuse scattering of point defects see [107][108][109][110][111][112][113][114][115][116].…”
Section: Vacancies and X-ray Line-profile Analysis 377mentioning
confidence: 99%
“…Many observations of intensity maxima displaced from reciprocal-lattice-point positions have been reported and discussed in the literature. Notable examples include the diffuse scattering associated with heavy radiation-damage effects in close-packed metals and oxides (Austerman & Miller, 1965;Keating, 1968;Nimura, 1955) and the diffuse scattering associated with the fie) transformations of various Ti and Zr alloys (Moss, Keating & Axe, 1973;Borie, Sass & Andreassen, 1973). In each case an analysis of the scattering in terms of the model we have used here provides an immediate indication of the type of fault involved and the approximate frequency of occurrence of the fault.…”
Section: Special Casesmentioning
confidence: 99%